Analisis Nilai Tambah Kopi Arabika Sipirok dengan Metode Basah dan Kering - Bima Kurnia Simatupang; Siti Mardiana; Rika Fitri Ilvira (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
The added value of coffee represents the difference between the selling price of processed coffee products and the cost of raw coffee beans used in production. This study aimed to analyze the added value and profit generated from processing Arabica coffee cherries into green beans, roasted beans, and ground coffee, comparing wet and dry processing methods at the Darul Mursyid Coffee Trading Unit in Simanosor Village, South Tapanuli Regency. Conducted from July to August 2023, this research utilized a descriptive quantitative approach with data collected purposively from two key informants: the heads of finance and production at PDM Coffee. The variables included processing methods (wet and dry) and their impact on added value and profitability. Data analysis employed the Hayami method (1987) for added value and an independent sample t-test for statistical comparisons. The study found that the added value for wet processing was IDR 8,623/kg (green beans), IDR 37,897/kg (roasted beans), and IDR 42,319/kg (ground coffee). For dry processing, the values were IDR7,195/kg, IDR 37,689/kg, and IDR 42,215/kg, respectively. The t-test indicated no significant difference in added value between the two methods (Sig. = 0.976, p > 0.05). Monthly profits from wet processing were IDR 99,851,000 (green beans), IDR20,423,500 (roasted beans), and IDR 6,298,500 (ground coffee), while dry processing yielded IDR78,936,000, IDR15,673,500, and 5,385,500, respectively.